Comparative study of tissue reactivity to n-butyl-2-cyanoacrylate and nylon monofilament thread on pericranium-cutaneous flaps in rats - Cavazana,William César (2014)
PURPOSE: To study the repair of pericranium-cutaneous flaps fixed with suture anchored in a skull bone tunnel or N-butyl-2-cyanoacrylate adhesive in Wistar rats with emphasis on the cellular inflammatory response and the production of types I and III collagen.METHODS: The operated region in the cephalic region of Wistar rats was removed minutes before euthanasia, fixed in formalin, and subjected to histological preparation. Slides were stained with hematoxylin-eosin and Picrosirius. Standardized counts of polymorphonuclear and mononuclear cells, fibroblasts, and macrophages were performed, and the percentages of types I and III collagen were determined. Data collection occurred on days 3, 7, 14, 21, and 45 postoperatively. A value of p<0.05 was considered statistically significant.RESULTS: Quantitative analysis of the data showed more fibroblasts in the surgical adhesive group than in the nylon monofilament thread groups (p=0.0211). Qualitative analysis showed higher reactivity in the adhesive group, with a predominance of polymorphonuclear cells from days 3-45 and macrophages from days 3-7. The amount of type I collagen exceeded 80% in the treated and control groups at the end of the experiment.CONCLUSIONS: Subperiosteal detachment triggers a cellular inflammatory response that is amplified using soft tissue fixation methods. The adhesive n-butyl-2-cyanoacrylate was more reactive than the nylon monofilament thread anchored in the skull bone tunnel.